Stress assessment and fracture surface analysis in a foreign object damaged 7075-T6 specimen under rotating bending. (August 2022) - Arcieri, Emanuele Vincenzo; Baragetti, Sergio; Božić, Željko
Highlights: The rotating bending fatigue failure of a damaged 7075-T6 specimen is studied. FEM and fracture surface analysis are used to understand the failure mechanism. Residual tensile axial stresses are one of the causes for fatigue crack initiation. Cracks also propagate from the surface of the dent caused by impact. The reduction in fatigue strength is 30 ± 10% compared to undamaged specimens. Abstract: The damage caused by impact of hard particles on aircraft components is called Foreign object damage (FOD) and it may cause premature failure. 7075-T6 is one of the alloys frequently used for manufacturing aircraft parts and components. In this paper, the failure mechanism of a damaged 7075-T6 specimen subject to rotating bending was explained from a phenomenological point of view using the Finite Element (FE) method and the fracture surface observation. The results showed that the crack initiation occurred in the locations of the highest residual tensile axial stresses after the impact, where also the tensile axial stresses in the simulated fatigue cycle are the highest, and at the surface of the FOD dent. A discontinuity was observed under the dent, in the area subject to compression after the impact and in the fatigue cycle. The damage induces a 30 ± 10% reduction in fatigue strength compared to undamaged specimens.